REFORMULASI KONSEP DAKWAH DI ERA MODERN (Kajian tentang Dakwah tehadap Ahl al-Kitāb) - Ramli Ahmad (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2016)
In this modern era, dakwah activities must keep abreast of the times, including the concepts and methods used. Da'wah is used for this must be reformulated in accordance with the times. Similarly, the public is often called the Ahl al-Kitab (Nasrani and Yahudi), although it has done deviations agains this own holy book, so that their holy book is not pure anymore. Christians assume that Jesus was the son of God, as well as Jews assume that Uzayr is the Son of God. And they deny the coming of the last Prophet, the Prophet Muhammad. as described in their scriptures. That to realize there formulation da'wah of the Ahl al-Kitab. It is necessary to create harmony among religions depends on the willingness to improve relations in order to organize the future in to a better direction. So that constructive dialogue is necessary to build a community that has a concern. In addition, Muslims must be a lamp to the followers of the other. Various concepts and methods offered in the Quran and the Hadith of the Prophet in delivering dakwah appeal against the Ahl al-Kitab. Such as bi al-hikmah, al-Mauizah, al-Muja>dalah, and tolerance a sever exemplified by the Prophet.